As práticas educativas da Liga Camponesa de Sapé: memórias de uma luta no interior da Paraíba (1958-1964) - Xavier, Wilson José Félix (2010)
This research discusses the conceptions and educational practices of the Ligas Camponesas da Paraíba, and in particular of the Liga Camponesa de Sapé, reflecting on the possibility of the association have become a "place of education", i.e., a space initiatives bringing together formal and informal education as an aspect of peasant struggle against the exploitation of the block agro-industrial state in the 1960s. This involved a raid on the complex negotiations and political-educational experiences of major social movement that has taken between the years 1958-1964 (period of operation of that organization) in Paraíba. It consists of a study that used, among other sources, thematic interviews with former members of the Liga Camponesa de Sapé, with reference to theoretical and methodological perspective of the Social History of England, more specifically working with the category of "experience" Thompson, in a constant dialogue with Benjamin's critique of the notion of time "empty and linear." The work of political education developed by the Liga de Sapé in different places to fight identified - the headquarters of the Liga, assemblies, cirandas , rallies, radio schools, crop circles - has influenced the knowledge and everyday doings of the peasants, suggesting new avenues of resistance . This recall / reconstruction opens new possibilities for understanding the phenomenon Ligas Camponesas.